Analisis Strategi Pengembangan Agribisnis Kopi Arabika di Kelurahan Bontolerung Kecamatan Tinggimoncong Kabupaten Gowa - Hasriani Hasriani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The opportunities and difficulties encountered are directly correlated with the expanding potential of Indonesia's coffee industry. One of South Sulawesi Province's areas, Gowa Regency, can produce Arabica coffee varietals with the best flavour. In the 2021 Indonesian Cup of Excellence ranking, Arabica coffee from Bontolerung Village, Tinggomoncong District, Gowa Regency, is ranked in the top 10. A number of challenges are in the way of this success, including a lack of suitable transportation options to the region where the coffee is collected. Arabica, low productivity due to robusta and blended coffee dominance, weak farmer institutions, the only way to sell arabica coffee is as whole beans with no further processing, and little capital and marketing, in Bontolerung Village, Tinggimoncong District, Gowa Regency, different development strategies for The Arabica coffee growing industry is the result of this research. The study was conducted in November and December 2022. Twenty-four coffee producers and five other associated stakeholders comprised the sample of respondents for the study. To formulate a Coffee Agribusiness Development Strategy Arabica, the data analysis technique used is descriptive analysis with IFAS, EFAS, and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis data to identify internal factors (strengths and weaknesses), as well as external factors (opportunities and threats). The study's findings are categorized under quadrant I, characterised by an aggressive (growth-oriented) strategy. Due to the numerous chances it offers, this position denotes that Bontolerung Village Arabica coffee is beneficial for growth and expanding business. Based on the results of the SWOT analysis, the government should support the growth of Arabica coffee agribusiness activities through appropriate policy and service and by increasing the marketing of Arabica coffee in both its raw and processed ground forms.